KUALITAS PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH M. YUNUS BENGKULU - Yusuarsono - (Professional: Jurnal Komunikasi dan Administrasi Publik, 2014)
Based on the preliminary survey I conducted at RSUD M. Yunus  Bengkulu, there were a number of patients who complained to the  services  provided by the inner  disease clinic. They were unsatisfied with the readiness of  officials  in giving services and the irregular schedule  for medical check –up. They  also complained with the time provided by the officials  in giving services, which was too short, i.e. starling from 8.00 to 11.30 west  Indonesia time. Indeed, the officials often give services star from 9.00 (one hour delay from the schedule), so that the patients felt that the officials  carried  out the services unprofessionally. This research aims to describe  the quality of services provided  by the nurses, doctors, and administrative  staff in the clinic of inner disease at M. Yunus hospital, Bengkulu. Samples in this research were selected by using accidental sampling method. The data were collected using questionnaire. The collected data that were then analyzed using descriptive  qualitative method. The finding shows that the services provided by both nurses and administrative  staff were not satisfying. The medical services provided by the doctors in contras were in good quality.Keywords : quality service of nurses, doctors, and administrators.